Student Teachers’ Didactic Choices and Motives when Designing Digital Competence Education: Pupils’ Age as a Didactic Dimension - Carolina Martínez (Educare)
This study furthers the understanding of how student teachers make didactic choices when designing digital competence education. It investigates what age groups student teachers choose to include in digital competence education, how they motivate these choices, and how their choices can be understood within the context of the university course in which they designed this education. The material includes 48 papers written by student teachers within a Swedish university course in which they each designed a project intended to promote digital competence among pupils in school-age educare (children aged 6 to 12 years). These papers were analyzed using a mixed-method approach involving both qualitative and quantitative analysis. The perspectives on age as a didactic dimension developed by Klafki and Comenius and the concept of boundary-work were used as a theoretical framework to analyze student teachers’ didactic choices. The results show that students most commonly choose to include older pupils, namely those in Grade 3 and 4 (9–10-year-olds), while paying less attention to the younger pupils. They motivated their choice of age groups based on arguments related to three key themes: children’s media use, children’s capacities, and their own future needs and circumstances as teachers. One implication of the study is that teacher education courses on digital competence should emphasize age as a didactic dimension and encourage student teachers to critically reflect on their assumptions about children’s age and capabilities.